Factors to consider in the transition from a teacher-centred model to a learner-centred model in a computer-rich learning environment - Cronje, Johannes Christoffel (University of Pretoria, 2013)
Dissertation (MEd(Computer-integrated Education))--University of Pretoria, 2005.